2023
DOI: 10.1111/1753-0407.13348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium‐glucose cotransporter 2 inhibitors on the rate of decline in kidney function: A systematic review and meta‐analysis

Abstract: Aim To investigate the influence of sodium/glucose cotransporter‐2 inhibitors (SGLT‐2i) on renal function during the course of its administration, particularly in the initial weeks. Materials and Methods Randomized controlled trials (RCTs) related to SGLT‐2i were searched in databases (MEDLINE, EMBASE, and Cochrane Central Register) from the database's inception to August 31, 2021. All RCTs reported the kidney outcomes of SGLT2i versus active or placebo control were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
(117 reference statements)
2
8
0
Order By: Relevance
“…Renal concentrations of antioxidants, IL-10, and adiponectin increased, whilst the oxidative stress markers, proinflammatory cytokines, leptin, resistin, TGF-β, iNOS, NGAL, and KIM-1 declined with both monotherapies compared to the PC animals. Our findings are aligned with many reports that have underscored the beneficial nephroprotective effects of SGLT2i [15,[20][21][22] and Pcal [24,[27][28][29] that could include glycaemic control with inhibition of renal lipotoxicity, oxidative stress, and inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Renal concentrations of antioxidants, IL-10, and adiponectin increased, whilst the oxidative stress markers, proinflammatory cytokines, leptin, resistin, TGF-β, iNOS, NGAL, and KIM-1 declined with both monotherapies compared to the PC animals. Our findings are aligned with many reports that have underscored the beneficial nephroprotective effects of SGLT2i [15,[20][21][22] and Pcal [24,[27][28][29] that could include glycaemic control with inhibition of renal lipotoxicity, oxidative stress, and inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…Others have also shown that SGLT2i increased β-cell mass and insulin production by simultaneously inducing proliferation and inhibiting apoptosis in the pancreas of diabetic animals [47,48]. In clinical settings, SGLT2i also reduced albuminuria, modulated the levels of adipokines, and slowed the progression of chronic kidney disease [15,[20][21][22]. On the other hand, the synthetic analogue of active VD 3 , Pcal, also exerted antidiabetic actions by increasing insulin production following impedance of oxidative stress and inflammation of pancreatic β-cells in rats injected with STZ [49].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Loss of tubular gluconeogenesis and a switch to glycolysis are known pathologic features of CKD [ 23 ]. In clinical trials, SGLT2 inhibitors were effective to attenuate the deterioration of kidney function in CKD patients [ 24 ].…”
Section: Cadmium the Liver Kidney And Diabetes Typementioning
confidence: 99%